The Use Word Card Media to Improve Reading Skills of Elementary School Students: A Literature Review - Umi Ningsih; Yasinta Mahendra; Sumarno (Universitas Pendidikan Ganesha, 2025)
Low reading proficiency among elementary school students remains a persistent challenge in early education. This research aims to share empirical evidence regarding the effectiveness of implementing word card media to improve students' reading skills. This media can be an interesting strategy to apply in Indonesian language learning. This research uses the systematic literature review (SLR) technique with a literature review method explaining that SLR or systematic literature review is research used in the field of research and development and also refers to research methodology and also measurements related to focus on a particular topic, research results based on the keyword